2023
DOI: 10.3389/fmolb.2023.1192794
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of photosensitizers: arrangement in bacterial membrane matters

Abstract: Porphyrins are well-known photosensitizers (PSs) for antibacterial photodynamic therapy (aPDT), which is still an underestimated antibiotic-free method to kill bacteria, viruses, and fungi. In the present work, we developed a comprehensive tool for predicting the structure and assessment of the photodynamic efficacy of PS molecules for their application in aPDT. We checked it on a series of water-soluble phosphorus(V) porphyrin molecules with OH or ethoxy axial ligands and phenyl/pyridyl peripheral substituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The presence of a restriction enzyme in bacteria could play a vital role in cleaving the phosphodiester bonds of DNA molecules through the formation of hydrogen bonding between the hydrogen atom of water molecules and the oxygen atom of the phosphodiester bonds. Other studies, however, demonstrated that metalloporphyrins might also be used in photodynamic therapy (PDT) as antibacterial agents. In a PDT system, light excites the porphyrins, which then generate free radicals, particularly reactive oxygen species, that cleave biomolecules, including DNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a restriction enzyme in bacteria could play a vital role in cleaving the phosphodiester bonds of DNA molecules through the formation of hydrogen bonding between the hydrogen atom of water molecules and the oxygen atom of the phosphodiester bonds. Other studies, however, demonstrated that metalloporphyrins might also be used in photodynamic therapy (PDT) as antibacterial agents. In a PDT system, light excites the porphyrins, which then generate free radicals, particularly reactive oxygen species, that cleave biomolecules, including DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, demonstrated that metalloporphyrins might also be used in photodynamic therapy (PDT) as antibacterial agents. 50 54 In a PDT system, light excites the porphyrins, which then generate free radicals, particularly reactive oxygen species, that cleave biomolecules, including DNA.…”
Section: Introductionmentioning
confidence: 99%
“…A series of water-soluble phosphorus(V) porphyrin molecules with OH or ethoxy axial ligands and phenyl/pyridyl peripheral substituents were used as antimicrobial agents in two Gram-negative bacteria models, such as Escherichia coli ( E. coli ) and Acinetobacter baumannii ( A. baumannii ). These porphyrins with an extremely low light dose of 5 J/cm 2 in MIC 50 values fight against COVID-19, based on the molecular interaction between phosphorus(V) porphyrin and bacterial lipid membranes [ 11 ]. The photodynamic therapy with Tetrahydroporphyrin-tetratosylate photodynamic therapy (THPTS) was also used to prevent the infection of COVID-19 with a virus load-reducing effect only at a higher concentration of 3 µM upon near-infrared light irradiation (760 nm, 3.9 or 7.8 J/cm 2 ), which reduced the viral load in vivo, deactivated SARS-CoV-2 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%